DEVELOPMENT OF AN EFFECTIVE METHOD FOR ISOLATING OF HYDROPHOBIN-TYPE PROTEINS FROM TRICHODERMA VIRIDE SUBMERGED CULTURE AND EVALUATION OF THEIR PROPERTIES - NIKITA KHRAPATOV; BORIS KOLESNIKOV; MARK SHAMTSYAN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry, 2019)
Hydrophobins are low-molecular proteins with very high surface activity and great potential for application in food and pharmaceutical industries. In this study an efficient method for isolation of hydrophobin-type proteins from Trichoderma viride mycelia biomass and native liquid of culture medium was elaborated. Extraction buffer and parameters of the extracting agents, such as buffer pH value and its molarity, as well as extraction temperature and duration time were selected. Obtained proteins were purified and their molecular weight was determined as 8 ± 1 kDa. Surface active and foam stabilizing activities of obtained proteins were also determined. Surface activity of isolated hydrophobin-type proteins was compatible to the activity of sodium dodecil sulfate, while foam stabilizing effect was higher and the action was much longer then when sodium-caseinate or Tween-80 were used.